1987
DOI: 10.1177/089484538701400206
|View full text |Cite
|
Sign up to set email alerts
|

Teachers and Their Careers: Why Do They Choose Teaching?

Abstract: There isn't a day that goes by that somebody doesn't ask me why I chose teaching as a career. I am simply convinced that my interest in children and their well-being played a larger role in my decision making than anything else. I know I can make the world better due to my efforts--A 45-year-old high-school teacher.The above quote represents one of the central reasons why individuals choose teaching as a career. For years society has taken issue with public education without focusing enough attention on the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 2 publications
0
7
0
2
Order By: Relevance
“…Several existing studies have used the COI for the above purposes. DeLong (1987) administered the COI to individuals who entered the teaching profession and later made specialty choices within the field. He found that individuals who went into teaching reported a variety of career anchors and assigned different weights to these anchors.…”
Section: Use Of Coi In Existing Research and Practicementioning
confidence: 99%
“…Several existing studies have used the COI for the above purposes. DeLong (1987) administered the COI to individuals who entered the teaching profession and later made specialty choices within the field. He found that individuals who went into teaching reported a variety of career anchors and assigned different weights to these anchors.…”
Section: Use Of Coi In Existing Research and Practicementioning
confidence: 99%
“…Further, individual interests are associated with students' likelihood of being engaged in future tasks related to those individual interests, their task‐specific self‐efficacy, and their sparked and maintained situational interests (Chen et al, ; Durik & Harackiewicz, ; Hidi & Harackiewicz, ). For recruiting preservice teachers into a teacher education program, this entails appealing to potential candidates' past experiences and interests through outreach efforts that connect the program's goals to their past experiences and interests (DeLong, ; Haberman, ; Javornik Krecic & Ivanus Grmek, ; Parkay, Stanford, & Gougeon, ).…”
Section: Introductionmentioning
confidence: 99%
“…mesleğin gerektirdiği niteliklerle örtüşen kişisel özellikleri ifade etmektedir (Kyriacou ve Coulthard, 2000). Öğretmenlik mesleğini tercihte etkili olan içsel sebeplerden bazıları konu alanına ilgi duymak (Kyriacou, Hultgren ve Stephens, 1999), çocuklarla birlikte çalışmayı sevmek (DeLong, 1987;Krečič ve Grmek, 2005;Kyriacou vd., 1999;Richardson ve Watt, 2006;Saban, 2003), öğretmeyi sevmek (Boz ve Boz, 2008;Çermik vd., 2010), mesleğin gerektirdiği kişisel gelişim fırsatını kullanmak (Yong, 1995), çocukları sevmek, kişiliğin mesleğe uygun olması (Çermik vd., 2010(Çermik vd., , Özsoy, Özsoy, Özkara ve Memiş, 2010Saban, 2003) ve öğretmen olmaya istekli olmak (Bastick, 2000;Yong, 1995) şeklinde ifade edilmektedir. Öğretmenlik mesleğini tercih üzerine yapılan çalışmalar, ekonomik istikrarın olduğu gelişmiş toplumlarda içsel sebeplerin diğerlerine göre daha belirleyici, ekonomik çalkantıların daha fazla olduğu toplumlarda ise dışsal sebeplerin daha etkili olduğunu göstermektedir (Bastick, 2000;Papanastasiou ve Papanastasiou, 1997).…”
Section: Introductionunclassified
“…Bu açıdan bakınca, "kutsal meslek" algısı yukarıda bahsedilen kalıp yargılara dayalı bir gerekçe olarak da görülebilir. Diğer taraftan araştırmalar, topluma hizmet etme (Çermik vd., 2010;Evans, 1993;Olashinde, 1972;Saban, 2003;Sinclair, 2008), çocukların başarılarına katkıda bulunma (Bastick, 2000;Kyriacou vd., 1999;Saban, 2003), geleneksel davranan öğretmenlerin yerine geçme (Çermik vd., 2010;Sinclair, 2008), çocukları okuldan soğutan kötü uygulamaları değiştirme (DeLong, 1987;Şahin, 2014), sosyal eşitliği sağlama (Richardson ve Watt, 2006) konularındaki istek ve arzuyu gösteren birçok olumlu özgeci sebep ortaya koymaktadır. Sosyal bilgiler öğretmen adaylarının meslek tercih sebeplerini nasıl yorumladıklarını inceleyen bir çalışmada Şahin (2014), katılımcıların, öğretmenlik mesleği yoluyla dört boyutta değişimi ve dönüşümü hedeflediklerini saptamıştır.…”
Section: Introductionunclassified